DAPUR KOMUNITAS SEBAGAI MEDIUM REGENERATIF SOSIAL DAN LINGKUNGAN DI KAWASAN PERMUKIMAN AIR KAMPUNG APUNG - Tantheo, Richard; Sutanto, Agustinus (Jurusan Arsitektur dan Perencanaan, 2025)
Kampung Apung is an urban village located in West Jakarta, much of which is now submerged under water. This village was formerly known as Tanah Bengkok, an area that served as a cemetery for Chinese and Malay ethnic communities. In the 1960s, due to the urgent need for housing, local residents began settling along the edges of the cemetery, gradually forming a residential area called Kapuk Teko. Then, in 1979, industrial development led to excessive land filling around the settlement. This land filling created a basin-like depression in the Kapuk Teko area. As a result of continuous flooding and the lack of water drainage from this basin, water has remained stagnant permanently, causing the settlement to become known as Kampung Apung, or the